นวนิยายของนะญีบ มะห์ฟูซ : ผลกระทบของจักรวรรดินิยมที่มีต่อการเมืองและสังคมอียิปต์ - นารีมา แสงวิมาน (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
According to study, The Cairo Trilogy portrays the picture of political movements in the colonial period and after the independency period, In order to show the changes within the political sphere with the interference of the west, especially, the political battles against imperialistic powers in forms of movements, e.g. the Nationalists, the Muslim Brotherhood, the Communists and the Fascists. The Day the Leader Was Killed reflect the politic and economic crisis in the Infitah period when Egyptian people face with poverty, hardship, excessive debts, as well as the problem of corruption among politicians who rule the country. The author also shows the impact of Western culture which has created various changes in Egyptian culture and society. Traditional faiths and beliefs have been undermined. Some of the new generations have gradually adopted Western lifestyle as their pattern of living. Materialism and consumerism have widespread. However, the author emphasizes that the demoralization will never occur if people exercise wisdom and intelligence in life. These changes in Egyptian society under Westernization have created not only bad results. Good results of these changes include improvement in education, occupation and women rights.